ReThinking Management : Perspectives and Impacts of Cultural Turns and Beyond - Küpers, Wendelin; Sonnenburg, Stephan; Zierold, Martin (Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2017)
This book assembles multi-disciplinary contributions to delve deeper into ReThinking Management. The first part provides some foundational considerations and inspirations. Further chapters offer more specific links to the arts and creativity sectors as well as empirical research and case reflections. ReThinking Management pursues the main idea that management theory is not merely a sub-discipline of economics, but rather a cross-disciplinary and critical field of research and practice, with a decidedly cultural perspective. While questioning the status and practices of conventional management, the book opens up for new understandings, turns and perspectives. Contents ReThinking Management and Cultural Turns Culture and Creativity Applications and Activities Target Groups Researchers, lectures and students of social sciences, cultural studies and management studies Practitioners from different fields of business and management The Editors The editors are professors at Karlshochschule International University in Karlsruhe, Germany. Wendelin Küpers is Professor of Leadership and Organization Studies. Stephan Sonnenburg is Professor for Branding, Creativity and Performative Management. Martin Zierold is Professor for Arts Management and Cultural Studies.
Keywords: Social sciences.; Economic sociology.; Cultural studies.; elektronické knihy; electronic books